Near‐peer question writing and teaching programme. (2nd October 2017) - Musbahi, Omar; Nawab, Fuzail; Dewan, Nishat I; Hoffer, Alexander J; Ung, James FCC; Suleman, Muhammed Talha
Summary: Background: Near‐peer assisted learning (NPAL) is an increasingly important tool in medical education; however, although numerous published papers discuss its merits, the evidence on the effectiveness and student perception of NPAL is limited. We describe a novel near‐peer question writing and teaching programme to assess whether it improves the confidence of first‐year medical students for their first In‐Course Assessment (ICA) in medical school. The evidence on the effectiveness and student perception of NPAL is limited Methods: A team of medical students designed a question development procedure and a structured teaching programme. A total of 280 first‐year medical students were invited to appraise the questions. A questionnaire assessing confidence and student perception was sent to participants at different time points leading up to and after their first ICA at the medical school. Statistical analysis was performed usingspss 20. Results: One hundred and seventy one students attempted the questions. Students felt more confident with short‐answer questions (SAQs; 95% CI 1.5–2.0, p < 0.05) and multiple‐choice questions (MCQs; 95% CI 1.0–1.5, p < 0.05), as assessed using the Wilcoxon signed‐rank test. Overall, students were satisfied with the NPAL questions and teaching programme following their university examinations (p > 0.01). Conclusion: The NPAL project highlighted a trend towards improving students' confidence. Furthermore, the question writing and teaching programme can be used as a guide to confidently hold teaching sessions in the future. The NPAL project further reinforces existing published papers that have shown NPAL to be a powerful adjunct to existing undergraduate medical education.